Chitosan/dextran sulphate sodium hydrogels for wound healing material: preparation, characterisation andin vitroevaluation - Mansuroglu, Banu; Kizilbey, Kadriye; Sayan Poyraz, Fatma; Yurttas, Zuhal; Fuerkaiti, Sumeyra Nur; Abaoglu, Ipek Yagmur; Basat, Hatice Nursah (TAYLOR & FRANCIS LTD, 2021)
In recent years, the usage of hydrogels in tissue regeneration and controlled drug release systems have been increasing rapidly due to their water holding capacity and 3D structure. In this study chitosan and dextran sulphate sodium were prefered to form pH-sensitive hydrogel by physical interaction. The biodegradability of the chitosan and the therapeutic properties of dextran sulphate sodium make them suitable as wound dressing material. In addition to these good specifications of polymers, vitamin-C and quercetin, which have an accelerating effect on wound healing. The structural and morphological characterisation of hydrogels were performed by FT-IR and SEM. The sweeling behaviour of this hydrogel was examined in PBS at different temperatures (25 degrees C and 37 degrees C) and pHs (6,7,7.4,8). In vitro release pattern of quercetin and vitamin-C were investigated. It was seen from this experiment that at the end of the 7 days, cell viability on loaded and unloaded hydrogel were higher than control group.
Keywords: Hydrogel; wound dressing; chitosan; dextran sulphate sodium; vitamin C; quercetin; NANOHYDROXYAPATITE COMPOSITE SCAFFOLDS; BIODEGRADABLE HYDROGEL; MECHANICAL-PROPERTIES; TISSUE; Materials Science